KETERTARIKAN LALAT BUAH (Batrocera sp) TERHADAP WARNA PERANGKAP PADA PERTANAMAN SEMANGKA - Haerul Haerul; Andi Herwati (Jurnal Agrotek Tropika, 2023)
This study aims to determine the interest of watermelon oriental fruit flies in several trap colors. The study used a randomized block design (RAK), which consisted of 5 treatments and 3 replications. The treatment applied is the use of traps with different colors, namely; traps without color (clear), green, yellow, blue and red. Observations were made on oriental fruit fly populations in two phases of watermelon development, namely the vegetative growth phase (age 15 DAP to 30 DAP) and the generative growth phase (31 DAP to 60 DAP). This study showed that the use of color traps had no significant effect between treatments, but the results showed that in the watermelon vegetative growth phase, the use of red traps attracted more oriental fruit flies, i.e. an average of 65.3 tails compared to traps without color (clear), green yellow and blue. While in the watermelon generative growth phase, the use of green traps attracted more oriental fruit flies, i.e., an average of 95 tails compared to traps without colors (clear), yellow, blue and red.